Supporting teachers and children in schools: the effectiveness and cost-effectiveness of the incredible years teacher classroom management programme in primary school children: a cluster randomised controlled trial, with parallel economic and process evaluations - Ford Tamsin; Edwards Vanessa; Sharkey Siobhan; Ukoumunne Obioha C; Byford Sarah; Norwich Brahm; Logan Stuart (BMC, 2012)
Abstract Background Childhood antisocial behaviour has high immediate and long-term costs for society and the individual, particularly in relation to mental health and behaviours that jeopardise health. Managing challenging behaviour is a commonly reported source of stress and burn out among teachers, ultimately resulting in a substantial number leaving the profession. Interventions to improve parenting do not transfer easily to classroom-based problems and the most vulnerable parents may not be easily able to access them. Honing teachers' skills in proactive behaviour management and the promotion of socio-emotional regulation, therefore, has the potential to improve both child and teacher mental health and well-being and the advantage that it might potentially benefit all the children subsequently taught by any teacher that accesses the training. Methods/Design Cluster randomised controlled trial (RCT) of the Incredible Years teacher classroom management (TCM) course with combined economic and process evaluations. One teacher of children aged 4-9 years, from 80 schools in the South West Peninsula will be randomised to attend the TCM (intervention arm) or to "teach as normal" (control arm). The primary outcome measure will be the total difficulties score from the Strengths and Difficulties Questionnaire (SDQ) completed by the current class teachers prior to randomisation, and at 9, 18 and 30 months follow-up, supplemented by parent SDQs. Secondary measures include academic attainment (teacher report supplemented by direct measurement in a sub-sample), children's enjoyment of school, and teacher reports of their professional self-efficacy, and levels of burn out and stress, supplemented by structured observations of teachers classroom management skills in a subsample. Cost data for the economic evaluation will be based on parental reports of services accessed. Cost-effectiveness, using the SDQ as the measure of effect, will be examined over the period of the RCT and over the longer term using decision analytic modelling. The process evaluation will use quantitative and qualitative approaches to assess fidelity to model, as well as explore Head teacher and teachers' experiences of TCM and investigate school factors that influence the translation of skills learnt to practice. Discussion This study will provide important information about whether the Teacher Classroom Management course influences child and teacher mental health and well-being in both the short and long term. It will also provide valuable insights into factors that may facilitate or impede any impact. The trial has been registered with ISCTRN (Controlled Trials Ltd) and assigned an ISRCTN number ISRCTN84130388. (http://www.controlled-trials.com/isrctn/search.html?srch=ISRCTN84130388&sort=3&dir=desc&max=10)